Microstructural changes of the vestibulocochlear nerve in patients with Ménière's disease using diffusion tensor imaging - Yuan, Xiaojia; Li, Xiaozhen; Xu, Yu; Zhong, Liqun; Yan, Zhanfeng; Chen, Zhengguang (Frontiers in Neurology, 2022)
Objective To evaluate the microstructural changes of the vestibulocochlear nerve in patients with Ménière's disease. Methods A total of 26 subjects, 13 patients with MD and 13 healthy controls, underwent diffusion tensor imaging (DTI) on a 3T scanner. The independent sample t-test was used to compare the differences in fractional anisotropy (FA) and apparent diffusion coefficient (ADC) between the two groups. A Pearson correlation was used between DTI and the dizziness handicap inventory (DHI) scores. Results There was a significant decrease in FA and an increase in ADC of the vestibulocochlear nerve in MD patients compared with healthy controls (P = 0.04, P = 0.001). FA had negative correlations with the DHI score (r = −0.62, P = 0.02) and DHI-functional score (r = −0.64, P = 0.02). Conclusion These results are the first evidence of possible changes in the microstructure of the vestibulocochlear nerves in patients with MD. DTI is a potential technique for evaluating the vestibulocochlear nerve in patients with MD.